2011
DOI: 10.1021/bi200945v
|View full text |Cite
|
Sign up to set email alerts
|

Photoproduction of Catalase-Insensitive Peroxides on the Donor Side of Manganese-Depleted Photosystem II: Evidence with a Specific Fluorescent Probe

Abstract: The photoproduction of organic peroxides (ROOH) in photosystem II (PSII) membranes was studied using the fluorescent probe Spy-HP. Two types of peroxide, highly lipophilic ones and relatively hydrophilic ones, were distinguished by the rate of reaction with Spy-HP; the former oxidized Spy-HP to the higher fluorescent form Spy-HPOx within 5 min, while the latter did so very slowly (the reaction was still not completed after 180 min). The level of photoproduction of these peroxides was significantly larger in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
5
21
0
Order By: Relevance
“…and Ca 2? at catalytic concentrations (Yanykin et al 2010(Yanykin et al , 2013Khorobrykh et al 2011). In this study, we experimentally verified the suggestion that molecular oxygen (rather than superoxide anion radical formed on the acceptor side of PSII) is directly involved in the donor-side photoinhibition of Mn-depleted PSII membranes.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…and Ca 2? at catalytic concentrations (Yanykin et al 2010(Yanykin et al , 2013Khorobrykh et al 2011). In this study, we experimentally verified the suggestion that molecular oxygen (rather than superoxide anion radical formed on the acceptor side of PSII) is directly involved in the donor-side photoinhibition of Mn-depleted PSII membranes.…”
Section: Introductionsupporting
confidence: 73%
“…It is accompanied by the formation of hydroperoxides, and it has been suggested that it may lead to the donor-side photoinhibition of PSII Yanykin et al 2010;Khorobrykh et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions of Spy-LHP with O 2 -c , alkyl hydroperoxyl radical, nitric oxide, and peroxinitrite are insignificant (Soh et al, 2007). Its reaction with H 2 O 2 is very slow and can be distinguished from that with LOOH by the measurement of fluorescence increase kinetics (Khorobrykh et al, 2011).…”
Section: Oxylipin Carbonyls Formed In H 2 O 2 -Stressed Cells Can Caumentioning
confidence: 99%
“…The supernatant was collected, and its fluorescence was measured with a spectrofluorometer (FP 8300; JASCO) with excitation at 524 nm and emission at 538 nm. To determine the amount of peroxides, a standard curve was prepared with the model LOOH m-chloroperbenzoic acid (Khorobrykh et al, 2011).…”
Section: Detection Of Loohs With Spy-lhpmentioning
confidence: 99%